Generation of space with П-shape steel frame set and its optimization - Kim, So In; Jong, Ju Hyok; An, Kwang Il; Ryang, Yu Song; Ri, Chang Min; Kim, Tae Song (International Journal of Architecture and Urbanism, 2025)
This paper describes the generation of steel frame space with multi-object optimization. Steel frame space motives from the stapler pins. A cluster of stapler pins has an infinite number of pins that can be a standard model module. These modules can adjoin with one another through the horizontal or vertical direction, parallel or cross direction. With every spin’s strength, they can support all structures and spaces, make more, complex spaces, and change their vision.